Tubular dentin formation by TGF‐β/BMP signaling in dental epithelial cells. (2nd March 2022) - Lee, Yoon Seon; Park, Yeoung‐Hyun; Seo, You‐Mi; Lee, Hye‐Kyung; Park, Joo‐Cheol
Abstract: Objectives: This study aimed to identify formation of tubular dentin induced by transforming growth factor‐β (TGF‐β) and bone morphogenic protein (BMP) signaling pathway in dental epithelial cells. Methods: We collected conditioned medium (CM) of rTGF‐β1/rBMP‐2‐treated HAT‐7 and treated to MDPC‐23 cells. The expression levels of odontoblast differentiation markers, KLF4, DMP1, and DSP were evaluated by real‐time PCR and Western blot analysis. To evaluate whether CM of rTGF‐β1/rBMP‐2 induces tubular dentin formation, we made a beagle dog tooth defect model. Results: Here, we show that Cpne7 is regulated by Smad4‐dependent TGF‐β1/BMP2 signaling pathway in dental epithelial cells. CM of rTGF‐β1/rBMP‐2 treated HAT‐7 or rCPNE7 raises the expression levels of KLF4, DMP1, and DSP in MDPC‐23 cells. When rTGF‐β1 or rBMP‐2 is directly treated to MDPC‐23 cells, however, expression levels of Cpne7‐regulated genes remain unchanged. In a beagle dog defect model, application of rTGF‐β1/BMP2‐treated CM resulted in tubular tertiary dentin mixed with osteodentin at cavity‐prepared sites, while rTGF‐β1 group exhibited homogenous osteodentin. Conclusions: Taken together, Smad4‐dependent TGF‐β1/BMP2 signaling regulates Cpne7 in dental epithelial cells, and CPNE7 protein secreted from pre‐ameloblasts mediates odontoblast differentiation via epithelial–mesenchymal interaction.